Double bronchodilation in chronic obstructive pulmonary disease: a crude analysis from a systematic review - Lopez-Campos, Jose Luis (Int J Chron Obstruct Pulmon Dis, 2017)
OBJECTIVE: The combination of a long-acting muscarinic antagonist (LAMA) and a long-acting β(2)-agonist (LABA) in a single inhaler is a viable treatment option for patients with chronic obstructive pulmonary disease (COPD). Here, we systematically review the current knowledge on double bronchodilation for the treatment of COPD, with a specific focus on its efficacy versus placebo and/or monotherapy bronchodilation. METHODS: A systematic review of clinical trials investigating LABA/LAMA combination therapies was conducted. Articles were retrieved from PubMed, Embase, and Scopus on June 26, 2016. We specifically selected clinical trials with a randomized controlled or crossover design published in any scientific journal showing the following characteristics: 1) comparison of different LABA/LAMA combinations in a single inhaler for patients with COPD, 2) dose approved in Europe, and 3) focus on efficacy (versus placebo and/or bronchodilator monotherapy) in terms of lung function, respiratory symptoms, or exacerbations. RESULTS: We analyzed 26 clinical trials conducted on 24,338 patients. All LABA/LAMA combinations were consistently able to improve lung function compared with both placebo and bronchodilator monotherapy. Improvements in symptoms were also consistent versus placebo, showing some lack of correlation for some clinical end points and combinations versus monotherapy bronchodilation. Albeit being an exploratory end point, exacerbations showed an improvement with LABA/LAMA combinations over placebo in some trials; however, scarce information was available in comparison with bronchodilator monotherapy in most studies. CONCLUSION: Our data show consistent improvements for LABA/LAMA combinations, albeit with some variability (depending on the clinical end point, the specific combination, and the comparison group). Clinicians should be aware that these are average differences. All treatments should be tailored at the individual level to optimize clinical outcomes.